Child Rights Perspective Against Children in Conflict with The Law - Farhana, Farhana; Mintarsih, Mimin; Miskiah, Siti (AMCA Journal of Community Development, 2025)
Children in conflict with the law need special treatment to avoid actions that can hinder the child's development and growth. Children in conflict with the law have human rights. The handling of children in conflict with the law is carried out based on human rights and principles in the best interests of the child. The purpose of the study is to examine the handling of children in conflict with the law in accordance with children's human rights so that children's human rights are protected. By using the literature research method. The Judiciary is the last step to deal with children in conflict with the law in accordance with the principle of last resort. Therefore, the handling of children in conflict with the law through a restorative justice approach is comprehensive and effective handling in accordance with the spirit of the Convention on the Rights of the Child in the present, thus the development of regulations adds responsive and prospective implementing regulations in responding to the era of disruption 4.0 and the era of society 5.0.